Meridel Le Sueur's Feminist Bildungsroman: When Class Meets Gender - Núñez Puente, Carolina (Atlantis)

(untitled) (Mount Saint Vincent University, 2006)
American and communist, Meridel Le Sueur's legacy is hardly known. On the contrary, Mikhail Bakhtin's work is currently being reread by feminist critics. Through a feminist Bakhtinian critical perspective, this article examines Le Sueur's forgotten The Girl as the feminist Bildungsroman Bakhtin only sketched out in an unpublished book.